Neuronal Plasma Membrane Integrity is Transiently Disturbed by Traumatic Loading - Gustavo R Prado; Michelle C LaPlaca (Neuroscience Insights, 2020)
The acute response of neurons subjected to traumatic loading involves plasma membrane disruption, yet the mechanical tolerance for membrane compromise, time course, and mechanisms for resealing are not well understood. We have used an in vitro traumatic neuronal injury model to investigate plasma membrane integrity immediately following a high-rate shear injury. Cell-impermeant fluorescent molecules were added to cortical neuronal cultures prior to insult to assess membrane integrity. The percentage of cells containing the permeability marker was dependent on the molecular size of the marker, as smaller molecules gained access to a higher percentage of cells than larger ones. Permeability increases were positively correlated with insult loading rate. Membrane disruption was transient, evidenced by a membrane resealing within the first minute after the insult. In addition, chelation of either extracellular Ca 2+ or intracellular Ca 2+ limited membrane resealing. However, injury following chelation of both extracellular and intracellular Ca 2+ caused diminished permeability as well as a greater resealing ability compared to chelation of extracellular or intracellular Ca 2+ alone. Treatment of neuronal cultures with jasplakinolide, which stabilizes filamentous actin, reduced permeability increases, while latrunculin-B, an actin depolymerizing agent, both reduced the increase in plasma membrane permeability and promoted resealing. This study gives insight into the dynamics of neuronal membrane disruption and subsequent resealing, which was found to be calcium dependent and involve actin in a role that differs from non-neuronal cells. Taken together, these data will lead to a better understanding of the acute neuronal response to traumatic loading.